Visualisation of bioluminescent Vibrio midae SY9 K811 in juvenile Haliotis midae abalone using non-invasive bioluminescence imagining - Moonsamy, Karusha (Department of Molecular and Cell Biology, 2014)
Includes bibliographical references.